SAFEGUARDS ATAS IMPOR BENANG DARI SERATSTAPEL SINTETIK DAN ARTIFISIAL BERDASARKANPERATURAN SAFEGUARDS: Safeguards on the Import Of Yarn Products of Synthetic And Artificial Staple Fibers Under Safeguards Regulations - Qonita, Leilani Tertia; Saleh, Rosdiana (AMICUS CURIAE, 2024)
The imposition of safeguards on the import of yarn products of synthetic and artificial staple fibers is based on regulations in the field of safeguards. Safeguards can be imposed if there is a surge in imported productsthat threatens the domestic industry. The problems in this research is: how is the evidence conducted by KPPI against the threat of serious injury or serious injury of products that are considered competitive andextension of safeguards on the import of import of yarn products of synthetic and artificial staple fibers.The method is qualitaive with the main data being secondary data through library research and supported by interviews which were then analyzed qualitatively and conclusions were drawn using the deductivemethod. The conclusion of this study is: it is proven that there is a threat of serious injury experienced by the domestic industry which is determined by analyzing all related indicators. An investigation into the extension of the BMTP is carried out in accordance with regulations in the field of safeguards. It is better for domestic industrial business actors and the government to work together to improve quality of the industry for the BMTP action period and the BMTP extension that has been determined so that a domestic industry is created that avoids the threat of serious injury or serious injury.